2020
DOI: 10.1002/pat.5093
|View full text |Cite
|
Sign up to set email alerts
|

Polymethylmethacrylate derivatives Eudragit E100 and L100: Interactions and complexation with surfactants

Abstract: Precipitation or coprecipitation of polyelectrolytes has been largely investigated. However, the precipitation of polyelectrolytes via addition of charged and non‐charged surfactants has not been systematically studied and reported. Consequently, the aim of this work is to investigate the effect of different surfactants (anionic, cationic, non‐charged and zwitterionic) on the precipitation of cationic and anionic polymethylmethacrylate polymers (Eudragit). The surfactants effect has been investigated as a func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…CTAB probably is due to the stability of micellar interactions. Changes in polymer conformation are due to the interactions with surfactant just be related in the literature for systems differences of this work 67–70 …”
Section: Resultsmentioning
confidence: 95%
“…CTAB probably is due to the stability of micellar interactions. Changes in polymer conformation are due to the interactions with surfactant just be related in the literature for systems differences of this work 67–70 …”
Section: Resultsmentioning
confidence: 95%
“…Eudragit E100, a cationic polymethylmethacrylate, destabilized micelles of sodium dodecyl sulfate (anionic surfactant) . In the same study, an anionic polymethylmethacrylate of Eudragit L100 did not affect stability of a cationic hexadecyltrimethylammonium bromide micelles . To the best of one’s knowledge.…”
Section: Results and Discussionmentioning
confidence: 81%
“…40 Another study indicated that change in cmc of cetyltrimethylammomium bromide was a little in 0.5−2.0% polyvinylpyrrolidone solutions.41 Eudragit E100, a cationic polymethylmethacrylate, destabilized micelles of sodium dodecyl sulfate (anionic surfactant).42 In the same study, an anionic polymethylmethacrylate of Eudragit L100 did not affect stability of a cationic hexadecyltrimethylammonium bromide micelles. 42 To the best of one's knowledge. there are no direct studies indicating effects of the polymers (Carbomer, PEO, and PEG) on the drug micelles (DTZ, IMIP, TA, and PA).…”
Section: Resultsmentioning
confidence: 99%
“…In the hemolysis bioassay, we observed that the low hemolytic activity depends on the concentration of each treatment (hemolysis was concentration-dependent), so the dose is directly proportional to the hemolytic damage. However, when we evaluated the treatments based on nanoparticles, it was possible to observe a significant reduction in the nanoencapsulated treatments, this may be because the Eudragit ® polymers are innocuous, and the low hemolytic activity is due to the release of the active ingredients or extracts to the medium where they are, or by mechanical stress during centrifugation (Ofridam et al, 2021). As can be seen in graph 3, Ber turned out to be the most active treatment presenting average hemolysis of 7.21 % (not encapsulated) and 2.77 % (NPs), when evaluated at 100 ppm, however, these results are below the data presented in Table 2 where we determined the IC 50 values, where for the case of BerNPs it was 0.24 (E. histolytica) and 0.71 (T. vaginalis) μg/mL, respectively.…”
Section: Discussionmentioning
confidence: 99%